Optimizing the performance of the “Working Group of Cibodas Biosphere Reserve Management Coordination and Communication” (Pokja KKP CBC) to achieve Sustainable Development Goals - Ika Rosmalasari (Universitas Pakuan, 2026)
This paper analyzes the suboptimal role of the Working Group of Cibodas Biosphere Reserve Management Coordination and Communication, also known in Bahasa as Kelompok Kerja Koordinasi dan Komunikasi Pengelolaan Cagar Biosfer Cibodas (POKJA KKP CBC) in supporting sustainable development in Cianjur Regency. Problem identification was conducted using the CGI (Controversy, Gap, Inconsistency) approach, revealing issues such as a non-transparent working group formation mechanism, disharmonious stakeholder relationships, and an unclear division of roles. The USG (Urgency, Seriousness, Growth) analysis revealed nine problems stemming from the three identified issues, with the highest priority being the lack of transparency in the working group formation (score 25). The root causes include insufficient socialization, the absence of clear documentation, and the formation process being merely an administrative formality. Consequently, this led to a dysfunctional organization, weak institutional capacity, and obstacles to achieving sustainable development goals. The most appropriate policy recommendation to address the lack of transparency in the working group formation mechanism is the formulation and establishment of formation guidelines, formalized through an official Regional Head Regulation or Regent Regulation. The existence of these guidelines is expected to optimize the roles, functions, and performance of the POKJA KKP CBC. Binding regulations will ensure that this policy serves not only as a moral commitment but also possesses legal force to guarantee transparency, compliance, and consistency of implementation across all working groups formed within Cianjur Regency.